Synthesis of 2‐Oxindoles from Substituted Indoles by Hypervalent‐Iodine Oxidation. Issue 12 (26th March 2018) - Jiang, Xinpeng; Zheng, Cong; Lei, Lijun; Lin, Kai; Yu, Chuanming
Abstract : A practical conversion of indoles into the corresponding 2‐oxindoles is achieved efficiently using a hypervalent iodine reagent. This oxidation is amenable to different substituted indoles, and allows the synthesis of a wide range of synthetically valuable substituted 2‐oxindoles in up to 90 % yield. Furthermore, Ropinirole, a drug used to alleviate the symptoms of Parkinson's disease, was synthesized in three steps in an overall yield of 44 % using this method. Abstract : The practical and efficient conversion of indoles into the corresponding 2‐oxindoles is achieved under neutral conditions using a hypervalent iodine reagent. This oxidation is amenable to different substituted indoles.